Implications of Reading Research for Classroom Teachers and Administrators - Berger, Allen ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
Questionnaires submitted to 454 Pennsylvania teachers indicated that only a small percentage utilize teaching ideas gained directly from reading research. Poor communication between researchers and teachers can be attributed to the underlying purposes for research and the methods through which it is disseminated. The undertaking of research projects is frequently motivated by a desire to satisfy requirements for graduation, promotion, or tenure, rather than a desire to contribute to the body of knowledge. In addition, researchers caring little for other views keep themselves and their students within the confines of their own disciplines, disregarding ideas from other schools of thought. Several things contribute to the problem--research writing is often unintelligible, students are encouraged to keep silent rather than express conflicting views, and teachers are seldom afforded contact with researchers through conferences. Improvement of reading research and instruction is dependent on respect for individual differences, the development of research centers for teachers and administrators, a focus on general as well as specific knowledge, and concern for community needs. (KS)
ERIC Note: Paper presented at the Sixth World Congress on Reading (Singapore, August 1976).
Educational level discussed: Elementary Secondary Education.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Communication Problems; Educational Needs; Elementary Secondary Education; Higher Education; Information Dissemination; Interdisciplinary Approach; Motivation; Reading Research; Research Needs; Research Problems; Speeches/Meeting Papers